The Impact of Employer Attractiveness on Job Application Intentions: Mediating Role of Organizational Reputation in Gen Z Student Community - Mumtaz, Shofia; Ariawaty, R. Rina (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates the impact of employer attractiveness on the intention to apply for jobs, with organizational reputation as a mediating variable, within the context of Generation Z students. The research focuses on Company X, a fast-moving consumer goods (FMCG) company, and utilizes the Gen Z student community “Komunitas Mahasiswa Batch 3” as its sample. As members of Gen Z increasingly value company reputation, values, and branding in their career decisions, understanding the mechanisms that drive job application intentions becomes crucial. A quantitative approach was adopted using a survey method, collecting data from 388 student respondents who had completed their project with the community. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach via SmartPLS 4.0. The findings reveal that employer attractiveness significantly and positively influences both organizational reputation and job application intentions. Moreover, organizational reputation is found to play a significant mediating role in the relationship between employer attractiveness and the intention to apply. These findings offer both theoretical contributions to the employer branding literature and practical insights for companies seeking to attract and retain young talent in a competitive labor market.